Damage Tolerance Assessment Towards Structure Integrity For C-130 Aircrafts Of Royal Malaysian Air Force - Arvinthan Venugopal; Roslina Mohammad; Saardin Abd Aziz (Journal of Advanced Research in Applied Mechanics, 2021)
Military transport aircraft are vulnerable to the destructive impacts of boundless exhaustion harm caused by cyclic loading and natural conditions in which the aircraft operates. These factors severely affect the aircraft structure's integrity and safety, material performance can be significantly degraded by these factors. The Air Force's aircraft's structural safety is a vital issue affecting aircraft airworthiness in the current era. Due to this alarming issue, the need for a thorough study is critical to determine the impact of structural fatigue on C-130 aircraft in the Royal Malaysian Air Force (RMAF) fleet. This study's methodology uses the correlation of years in service to accumulated fatigue and cyclic loading to study the concept of aircraft aging in military aircraft. The data provided by this C-130 aircraft through an audit is to determine the critical fatigue areas and flight load conditions. Finally, it uses the concept of crack mapping and statistics from the Aircraft Structure Defect Report provided by flying squadrons in the RMAF to evaluate the structural deterioration. This study contributes to a design change review of the current aircraft maintenance plan. Furthermore, this will be the platform to embark on the Aircraft Structure Integrity Program (ASIP) for the RMAF C-130 aircraft.